Work Compatibility of Loading Excavators and Conveying Equipment in The Stripping of Overburden Pc 2000 - Admizal Nazki; Heri Prabowo (CIVED, 2025)
The productivity of overburden stripping is highly dependent on the productivity and work compatibility of the mechanical tools used. This research was carried out on the work load excavator (Fleet 1825) at Pit Banko Tengah A, PT Bukit Asam (Persero) Tbk. with the aim of analyzing the productivity level of the excavation and loading equipment, determining the work compatibility value (match factor), and evaluating the number of transportation equipment needs. Based on actual observations, obstacles were found in the form of piles of soil (spoil) on the side of the road and undulating transport road surface conditions. Road conditions that do not meet these standards result in narrowing of lanes, a decrease in the average speed of means of transportation, and an increase in cycle time. This study uses a quantitative method with primary data collection which includes cycle time, effective working time, and the number of  digging and loading bucket fills. The results of the analysis showed that the actual productivity of the Komatsu PC 2000-8 excavator excavator reached 914.57 BCM/Hour, while the productivity of the Komatsu HD-785 Dump Truck was 164.7 BCM/Hour. The assessment of work compatibility between 1 unit of excavation equipment and 7 units of transport equipment resulted in  a Match Factor (MF) value of 1.25. The MF value of > 1 indicates the occurrence of queues and waiting times for transportation equipment in the work area. Based on the evaluation of productivity suitability, it is recommended to reduce the number of transportation equipment from 7 units to 6 units so that the production target runs optimally and efficiently. In addition to optimizing the compatibility of digging loading and transporting equipment, it is recommended to standardize the geometry of the transport road according to regulations to minimize obstacle time.